Randomised trial of a serious illness decision aid (Plan Well Guide) for patients and their substitute decision-makers to improve engagement in advance care planning. Issue 1 (30th June 2021) - Howard, Michelle; Elston, Dawn; Borhan, Sayem; Hafid, Abe; Arora, Neha; Forbes, Ruth; Bernard, Carrie; Heyland, Daren K
Abstract : Objective: To evaluate the feasibility and efficacy of a serious illness decision aid (Plan Well Guide) in increasing the engagement of substitute decision-makers (SDM) in advance care planning (ACP). Methods: This trial was conducted (2017–2019) in outpatient settings in Ontario, Canada, aiming to recruit 90 dyads of patients aged 65 years and older at high risk of needing future medical decisions and their SDM. Participants were randomised to receive the intervention immediately or to a 3-month wait period. The Plan Well Guide was administered to the patient and SDM by a facilitator. Outcomes were change on the validated 17-item SDM ACP Engagement Survey (primary) and 15-item patient ACP Engagement Survey (secondary). Results: Of 136 dyads approached, 58 consented and were randomised and 45 completed the study (28 immediate intervention, 17 delayed intervention). The trial was stopped early because of difficulties with enrolling and following up participants. The mean changes on the SDM ACP Engagement Survey and the patient ACP Engagement Survey favoured the first group but were not statistically significant (mean difference (MD)=+0.2 (95% CI: −0.3 to 0.6) and MD=+0.4 (95% CI: −0.1 to 0.8), respectively). In a post-hoc subgroup analysis, significant treatment effects were seen in SDMs with a lower-than-median baseline score compared with those at or above the median. Conclusions: In this statistically underpowered randomised trial, differences in SDM ACP engagement between groups were small. Further information is needed to overcome recruitment challenges and to identify people most likely to benefit from the Plan Well Guide. Trial registration number NCT03239639